Racism and Health II: A Needed Research Agenda for Effective Interventions. (August 2013) - Williams, David R.; Mohammed, Selina A.
This article reviews the empirical evidence that suggests that there is a solid foundation for more systematic research attention to the ways in which interventions that seek to reduce the multiple dimensions of racism can improve health and reduce disparities in health. First, research reveals that policies and procedures that seek to reduce institutional racism by improving neighborhood and educational quality and enhancing access to additional income, employment opportunities, and other desirable resources can improve health. Second, research is reviewed that shows that there is the potential to improve health through interventions that can reduce cultural racism at the societal and individual level. Finally, research is presented that suggests that the adverse consequences of racism on health can be reduced through policies that maximize the health-enhancing capacities of medical care, address the social factors that initiate and sustain risk behaviors, and empower individuals and communities to take control of their lives and health. Directions for future research are outlined.